Polypill treatments for cardiovascular diseases. (2nd January 2016) - Webster, Ruth; Rodgers, Anthony
Abstract : Cardiovascular disease (CVD) is the leading cause of mortality globally. Effective CVD preventive medications are available including statin, blood pressure-lowering and antiplatelet medications; however most people do not take these drugs long term. Fixed-dose combination pills ("polypills") have been shown, in several clinical trials, to improve adherence to these recommended medications, with corresponding improvements in risk factors such as blood pressure and LDL-cholesterol. In patients not taking all modalities of recommended CVD preventive therapies, polypill-based strategies could importantly contribute to global CVD control strategies. The largest benefits are seen in those who are under-treated at baseline, rather than those who are already taking the individual components separately: simplified step-up is more important than pill count reduction. Despite the potential benefits for patients and payers, only a few polypills are available due to market failure in the funding of research and development for affordable non-communicable disease medicines. Regulatory paradigms have focused on substitution indications among patients already taking component medications; however, this is the population that is likely to receive the least benefit from a polypill-based strategy. Greater health impact is likely if focus is given to patients who have indications for all polypill components, but currently do not receive the benefits of recommended medicines long term.